A study of surface receptors on rat T lymphocytes - Crocker, G; Newton, M; Martin, B; Crocker, Glenn (1991)
﻿ A double immunolabelling technique was developed to study microscopically the interactions between CD4, CD45 and the T cell receptor on the surface of rat T cells induced by the phenomenon of co-capping. It was found that both CD4 and CD45 passively co-cap with the actively capped T cell receptor, that the T cell receptor and CD45 passively co-cap with CD4, but that neither CD4 nor the T cell receptor co-cap with CD45. Co-crosslinking and active capping of CD45 with either the T cell receptor or CD4 prevented CD4 or the T cell receptor respectively, from passively co-capping. These experiments were extended to study the effects of particular antibody crosslinking conditions on T cell proliferation and tyrosine phosphorylation. A correlation was found to exist between receptor distribution and the effects of particular antibody combinations on proliferation and tyrosine phosphorylation. The significance of this with respect to T cell activation is discussed. Finally, an observation is reported concerning the failure of some cell lines to cap antibody-crosslinked surface molecules. Preliminary investgations into the nature and extent of the phenomenon are described.